Development of services for crime victims in Serbia - Nikolić-Ristanović Vesna (Temida, 2007)
The aim of this paper is to review and analyze the history of services for crime victims in Serbia. The development of services for crime victims is analyzed and then, on the basis of the evaluation of the results achieved and comparisons with the situation in the world, the recommendations for future development are given. The analyses is based on results of several surveys which in different ways dealt with services for crime victims in Serbia and Belgrade in the period between 1990 and 2006. .